Analisis Arah Kebijakan Sekolah Terhadap Penggunaan Gawai Android dalam Aktivitas Belajar Peserta Didik di Masa Pandemi Covid-19 - Aswar, Aswar; Syarif, Sulfian; Sulkipli, Sulkipli; Amirullah, Muhammad (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to analyze school policies on the use of smartphones in student learning activities during the Covid-19 pandemic. The research method used a qualitative approach with the type of empirical phenomenology research. The research subjects were obtained through a purposive sampling technique, amounting to 6 people, and this research was conducted online or by phone to teachers, principals, and parents of students. Meanwhile, data analysis used empirical phenomenological analysis techniques The results showed that there were 4 aspects analyzed, namely benefits, drawbacks, learning strategies, and parents’ expectations of smartphone-based learning for students. From these four aspects, the school policy directions for the use of smartphones in student learning activities are formulated, including: 1) school policies should provide opportunities for students to use smartphones as a learning tool; 2) school policy should always provide education and oblige weekly meetings between teachers and parents to evaluate the behavior and learning outcomes of students; 3) school policies should facilitate students in the form of learning quotas and provision of wifi so that students and teachers can access the internet properly; 4) school policies should oblige teachers to improve their digital pedagogy competence; 5) school policy should apply the blended learning method during the Covid-19 pandemic.